Predictors of recurrent cardiovascular events in patients with a single-vessel coronary artery disease after ST-segment elevation myocardial infarction - V. E. Oleynikov; E. V. Averyanova; A. A. Tonkoglaz; M. V. Lukyanova (Рациональная фармакотерапия в кардиологии)
Aim. To determine the predictors of recurrent cardiovascular events in patients after ST-segment elevation myocardial infarction (STEMI) and hemodynamicallysignificant stenosis only in the infarct-related coronary artery.Material and methods. The present study involved 151 patients with STEMI. The mean age of patients was 51 (95% confidence interval (CI), 41–61 years) years. One of the inclusion criteria of patients was significant stenosis exclusively in the infarct-related artery. All patients underwent a 24-hour Holter electrocardiography (ECG) monitoring with the analysis of heart rate turbulence (HRT), heart rate variability (HRV), ventricular late potentials and chronotropic load; two-dimensional (2D) echocardiography with the analysis of volumetric parameters and left ventricular ejection fraction; determination of brain natriuretic peptide (BNP). The follow-up duration was 144 weeks. Repeated cardiovascular events (acute heart failure, revascularization, repeated myocardial infarction, cardiovascular death) were analyzed as endpoints. Two groups of patients were identified depending on the recurrent event endpoints: “RE” group — 26 patients (17.2%) with registered recurrent cardiac events, and “ST” group — 125 patients (82.8%) without cardiovascular events in stable post-infarction period.Results. Initial BNP values were lower in the “ST” group (p48=0.0035, p96=0.004, p144=0.001). The intergroup differences demonstrate a higher concentration of BNP levels in the “RE” group both initially (p=0,001) and at the 96th week (p=0,04). Left ventricular ejection fraction was higher in the “ST” group (p=0,001) both initially and at the 144th week in contrast to the “RE” group: 48,9% (44,7-53,2) vs 44,2% (38,5-49,9) (p=0,009). Pathological HRT was also significantly higher in the “RE” group both initially (p=0,003) and by the 96th week of the follow-up (p=0,007), while HRV demonstrated low initial values with a slow tendency to restoration. There were following risk factors for recurrent cardiovascular events in patients in the post-infarction period: weight — relative risk (RR), 1.21 (95% CI, 1,01-1,46) (p=0,03); body mass index — RR, 0,56 (95% CI, 0,325-0,96) (p=0,046); chronotropic load — RR, 1,03 (95% CI, 1,02-1,12) (p=0,04); BNP — RR, 1,012 (95% CI, 1,003-1,08) (p=0,01); left ventricular end-systolic dimension (ESD) — RR, 1,04 (95% CI, 1,01-1,13) (p=0,36).Conclusion. There were following independent predictors of recurrent cardiovascular events in patients after STEMI: weight, body mass index, chronotropic load, BNP and ESD.